(untitled) (African Journal of Biomedical Research, 2019)
The fortune of any community is measured by the nutritional status of its children. The study ascertained prevalence of anthropometric indices of malnutrition, malaria and intestinal parasites; and associated factors of malnutrition among primary school children (6-12 years) in Nsukka, Nigeria. Multi-stage random sampling technique what to select 396 participants from five public primary schools in Nsukka. Age, height and weight measurements were used to determine their anthropometric indices. Structured questionnaire was used to obtain information on factors associated with malnutrition. Malaria and intestinal parasite determinations were carried out using thin blood film and wet mount direct methods, respectively. Data were analysed using chi-square and logistic regression. Thinness (13.0%), stunting (5.6%), underweight (1.3%), overweight (6.1%), obesity (2.1%), malaria (56.1%) and typhoid (36.6%) were prevalent. Toilet facilities used by 22.0%, 2.8% and 1.5% were pit latrine, bush system and bucket latrine, respectively. Intestinal parasites seen among respondents were Entamoeba histolytica (7.3%) and Ascaris lumbricoides (34.1%). Polyparasitism existed in 2.4% of respondents. Risk of being stunted for pupils whose mothers earned ≤ N30,500 were about six folds higher (RR=5.534; CI = 0.733 - 41.780) compared to those whose mothers earned >N30,500. Risk of being underweight for pupils whose mothers and fathers were unemployed were about four folds higher (RR=4.222, CI = 0.427 - 41.784; RR=3.78, CI = 0.385 - 37.012, respectively) compared to respondents whose mothers and fathers were employed. Socio-economic factors were seen to increase their risk to malnutrition.